Pemanfatan Lahan Terbatas Menggunakan Sistem Aquaponik di Desa Kawedusan Bersama dengan PKK Desa Kewedusan Tahun 2022 - Yogi Ferdy Irawan; Puput Widodo; Ibnu Prasetyo Widiyono; Wisnu Guntur Sutopo; Erick Burhaein; Mokhamad Parmadi; Alfiah Risky Azizah; Ervian Arif Muhafid; Agus Hadiatmo (Abdibaraya: Jurnal Pengabdian Masyarakat, 2022)
In general, catfish farmers in Kebumen Regency, especially in Kawedusan Village use commercial floating pellets as feed. The use of this feed has several advantages, one of which is the rapid and uniform growth of fish. However, most of the catfish farmers complained about the small profits they received. These benefits are not comparable to the amount of energy and costs that have been incurred, thus threatening the sustainability of the breeder’s business activities. Another problem faced by farmers is the rapid dirty water of the pool, so that the frequency of replacement of water increases, which in turn increases the cost of electricity. When the partner is late in replacing the pool water, it can cause catfish disease that is difficult to control. Dirty water also makes the growth of catfish disrupted because of decreased appetite. The solution offered is by conducting counseling, training and mentoring the cultivation of organic vegetables using the aquaponics method, preparation of simple bookkeeping, calculation of production costs, and product pricing strategies. Selected plants cultivated during the activity are mustard greens (caisim) and kale. Both of these vegetables are of interest to the surrounding community and are suitable to be planted in lowland areas such as Kebumen and have a short planting period (± 40 days). The output of this activity is in the form of improving the skills of partners in vegetable cultivation in an aquaponics manner, compiling simple bookkeeping, calculating production costs, and determining the selling.Keyword: training, aquaponics, land